1997
DOI: 10.1111/j.1432-1033.1997.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Mitochondrial Permeability Transition by Nitric Oxide

Abstract: The influence of nitric oxide on mitochondrial permeability transition (MPT) phenomenon was studied. NO was generated by photolysis of S-nitroso-N-acetylcysteine, AcCys(NO), with green light (2 = 550 nm). Two distinct effects of nitric oxide on rat liver mitochondria were identified. First, NO accelerated an onset of swelling in Caz'-loaded mitochondria in a cyclosporin-A-sensitive manner acting as an inducer of permeability transition. This was, apparently, a result of irreversible alteration of mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 54 publications
2
57
1
2
Order By: Relevance
“…31 This NO-induced protective effect may be related to inhibition of mPTP opening concomitant with reperfusion. 32 Thus, the current results suggesting that eNOS plays a role in isoflurane-induced postconditioning may again be related to inhibition of mitochondrial permeability transition through enhanced NO production. Further study will also be required to confirm this intriguing hypothesis.…”
Section: Discussionmentioning
confidence: 69%
“…31 This NO-induced protective effect may be related to inhibition of mPTP opening concomitant with reperfusion. 32 Thus, the current results suggesting that eNOS plays a role in isoflurane-induced postconditioning may again be related to inhibition of mitochondrial permeability transition through enhanced NO production. Further study will also be required to confirm this intriguing hypothesis.…”
Section: Discussionmentioning
confidence: 69%
“…Many reports have indicated that high levels of NO induce apoptosis in numerous cell types. Apoptosis appears to be mediated largely by an effect of peroxynitrite on mitochondrial permeability either directly 66,67 or through DNA damage with subsequent activation of the PARS pathway. 68,69 Through the mitochondrial permeability transition, cytochrome C is released, which is a signal for apoptosis.…”
Section: No In Apoptosismentioning
confidence: 99%
“…19). Finally, it has been reported that NO can either stimulate or inhibit the MPT in liver mitochondria, often depending upon experimental conditions and the source of mitochondria (23,24).…”
mentioning
confidence: 99%